Quality of Service on Passenger Satisfaction at PT. Gapura Angkasa at Sultan Hasanudin Makassar International Airport - Mursalim Nohong; Julius Jilbert; Muh. Ihsan (Scientia Integritas Utama, 2022)
Along with the development of the field of services and technology as well as changes in life patterns that are getting faster, so many activities must be carried out and demanded to be able to meet their increasingly complex needs. One of the factors that determine the level of success and quality of companies engaged in the service sector is the ability to provide services to customers. Services that are in accordance with expectations can provide services that are in accordance with expectations and can provide satisfaction for service users, because quality has a close relationship with customer satisfaction. What is the relationship between reliability, assurance, physical evidence, empathy, and responsiveness on passenger satisfaction? There are still few researchers who explore this question. Service quality is often used as a measure that the services offered by the company are able to meet the desires and expectations of customers. This study aims to examine and analyze the effect of the variable’s reliability, assurance, tangibles, empathy, and responsiveness on passenger satisfaction. This research was conducted at the Sultan Hasanuddin International Airport Makassar. The research method used is a descriptive survey method. Collecting data by distributing questionnaires to the respondents. The sample who is also the respondent used in this study is as many as 100 people. Sampling from the study population uses a stepwise sampling method, where the first step is to determine the predicted sample size of the population; second, determining the target sample randomly. The analysis technique uses multiple linear regression analysis. The results of the factor analysis show that reliability, assurance, tangibles, empathy, and responsiveness have a positive and significant effect on passenger satisfaction.